MANAJEMEN SEKSI PENDIDIKAN MADRASAH KEMENTERIAN AGAMA KOTA PALANGKA RAYA DALAM PENGUATAN KOMPETENSI KEPRIBADIAN GURU MADRASAH - Sari, Nurita; Siminto, Siminto; Sapuadi, Sapuadi (Hijri, 2025)
Education is a key factor in improving human resources (HR) quality to face global challenges. In the context of Islamic education, madrasahs play a strategic role in shaping students with strong character and competencies. Teacher competency, particularly personality competence, is crucial in ensuring effective learning. This study aims to analyze the management of the Madrasah Education Section of the Ministry of Religious Affairs in Palangka Raya City in strengthening the personality competence of madrasah teachers. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings indicate that the Madrasah Education Section applies management based on POAC (Planning, Organizing, Actuating, and Controlling) through various programs, such as training in collaboration with the Banjarmasin Training Institute, In-House Training (IHT), and the utilization of the PINTAR application for online learning. However, several challenges persist in program implementation, including limited resources, unequal access to technology, and varying levels of teacher comprehension. Therefore, more effective strategies are needed to optimize and sustain the enhancement of teachers' personality competencies, ultimately contributing to the quality of education in madrasahs.